Internalisasi Nilai-Nilai Moderasi Beragama Dalam Membentuk Kesalehan Sosial Siswa Di Sdn 4 Gelangkulon Sampung Ponorogo - Mutamimah, Duwi Habsari; Billah, Akbar Aisya; Fitri, Okta Maya; Sustiawan, Asis (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Social piety is a concept where humans not only obey religious rituals, but can also practice religious teachings and benefit the social environment. One way to form social piety is through religious learning at school. Researchers are interested in researching the location of SDN 4 Gelangkulon because that location there is visible religious pluralism in it. This research aims to describe and explain the internalization of religious moderation values in forming social piety at SDN 4 Gelangkulon. This research method uses descriptive qualitative research using a case study method or approach involving Religious Students and Teachers in the Sodong Gelangkulon Sampung Ponorogo hamlet as research subjects. The results of the research show that internalizing the values of religious moderation through religious learning can contribute and prove effective in forming students' social piety because religious learning contains the values of religious moderation which include justice, tolerance, non-violence, harmony, and mutual help.